Gudmund Hat - Feilberg, C. G. (Kuml, 1959)
GUDMUND HATT ln his work of measuring field boundaries in the heathland of Jutland Gudmund Hatt had always a student or a young postgraduate with him as his assistant. At one time I was this assistant, and from this period I recall a particular occasion. We were sitting eating lunch together on a stretch of moorland in east Vendsyssel. It was one of those beautiful autumn days when the clear sunshine lends warmth to all the colours of the landscape from dark green through brown to red-gold. Around us the low ridges spread their net over the heath. Scattered as though at random over the landscape were small oval mounds with a hollow along one side, sites where trees had been felled by storm, and in falling had pulled up the soil at one side with their roots, leaving for ever afterwards a scar in the surface of the ground. It may well have been hundreds of years since this wood was felled by the storm; and yet it had grown up to stand as a great forest, since the time when, in a distant past, the earth on that spot had been tilled. Scattered among the system of field boundaries we had found graves, which belonged to the people who once had cultivated that soil. Then Hatt began to talk of that people; even as we now sat here, so too had the farmers of the Iron Age sat out by their fields. Their talk had ranged widely, and among other sub jects they had discussed new and outlandish burial customs which were coming in from the south. These customs had now reached Himmerland, and they would certainly come to Vendsyssel. Would that be a good thing? It was as though the fields around us gradually filled with people as Hatt talked. There is much of the artist in Gudmund Hatt. He has written poetry, and in his youth short stories. As I see it, there is a connection between this and Hatt's other work. Undoubtedly the capacity for artistic creation has been the mainspring of Hatt's scientific work, the capacity of employing a controlled imagination to form a whole out of many fragments. In his patient collection of facts concerning the agriculture of a distant past, facts such as these field boundaries and all that was associated with them, he could pause and interject, "Now, would one investigate all this, if one couldn't see anything in it?'' This ability to see something in things has time and again shown itself in Hatt's scientific production. As a young research worker he had noticed certain peculiarities in the cut of the fur clothes of arctic peoples. He pursued these peculiarities from museum specimen to museum specimen. Other evidence appeared. There was a type of clothing and of tools, which appeared to be characteristic of peoples who lived on the coasts and based their livelihood on sea and river hunting. Another type of dress associated itself with snowshoes, which permitted men to hunt in the light loose snow of the winter forests. From all these observations grew up the theory of the two widely spread strata of culture which have influenced the life of the arctic peoples, the coast culture and the inland culture. Hatt has consistently possessed this intuitive grasp of coherence within the broad picture. I think here of his latest work within the field of primitive agriculture. In his treatise "Kornmoderen i Amerika og Indonesien" (The Corn Mother in America and Indonesia) he demonstrates by means of a large body of folklore ideas which were common to agriculturalists on both sides of the Pacific, and thereby adds weight to the theories which have also been put forward elsewhere (by Robert Heine-Geldern) of influences reaching from Asia to America in a period going back to the commencement of the Christian Era. It may seem almost a labouring of the obvious to point out how difficult the work of the researcher can be. Anyone who glances at a modem treatise on atomic physics will quickly realise that it requires a high degree of mathematical skill and a quite extraordinary ability to form a conception of things which it is almost impossible for human comprehension to grasp, to be able to treat of such a subject. But at least equally difficult is in truth the task of the historian. To understand, and in imagination to reconstruct, the way of life of men in an earlier historical period demands not only a fine technique of source-criticism but also a broad human experience and understanding such as only few are granted. And in this field a complete and final answer can never be given. That is one of the reasons why history must continually be rewritten. Great are the demands, too, made of the researcher into cultural geography. There is need not only for thoroughgoing investigation in many fields, but also for a considerable historical understanding, to be able to paint a picture of a people's culture in relationship to the physical environment in which they live. Hatt has always taken his work as cultural geographer and cultural historian with deep conscientiousness. I recall a conversation with him concerning a man who somewhat casually scattered broadcast theories and ideas concerning the past. Hatt was angry: such a man completely failed to understand how serious the tasks we set ourselves were, and he should be told so. Hatt embodied a gigantic labour in the cultural-geographical section which he wrote for the large four-volume work "Jorden og Menneskelivet" (The Earth and the Life of Man), which he published in the 1920's together with Martin Vahl. Despite the thirty years which have passed this work is still regarded with respect. When one has studied deeply some aspect of cultural geography, and is of the opinion that one has discovered new facts and viewpoints, then it often happens that, on returning to Hatt's work, one discovers that he has already in fact made the same observations. Seriousness is the badge of honour which marks Hatt's attitude to his researches, and there is no doubt that, when time has shaken much of what we in our day regard as the results of science, then no small part of Hatt's work will stand. C. G. Feilberg